2000
DOI: 10.1111/j.1475-4754.2000.tb00890.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods for Establishing Fatty Acid Concentration Gradients Across Potsherds: A Case Study Using Late Bronze Age Canaanite Amphorae*

Abstract: Canaanite amphorae fragments in fabrics believed to be associated with the bulk transport of vegetable oils from the fourteenth‐century BC site of Amarna, Egypt, have been examined. A comparison is made between solvent extraction, saponification and the use of TMTFTH (m‐trifluoromethylphenyl)trimethylammomum hydroxide, used here for the combined extraction and derivatization of ceramic‐absorbed organic residues. Extracts were studied using gas chromatography and gas chromatography‐mass spectrometry. The extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 28 publications
(30 reference statements)
2
56
0
1
Order By: Relevance
“…However, it has been noted that, although present in significant concentrations around the rim, these lipids exhibit a higher degree of degradation, probably due to their contact with air that promotes oxidation (Regert et al, 1999). Furthermore, it has been shown that concentration gradients exist between the inner and the outer surface of the sherds (Stern et al, 2000).…”
Section: B Samples and Sampling Protocolsmentioning
confidence: 98%
“…However, it has been noted that, although present in significant concentrations around the rim, these lipids exhibit a higher degree of degradation, probably due to their contact with air that promotes oxidation (Regert et al, 1999). Furthermore, it has been shown that concentration gradients exist between the inner and the outer surface of the sherds (Stern et al, 2000).…”
Section: B Samples and Sampling Protocolsmentioning
confidence: 98%
“…One study found low, but quantifiable, abundances of fatty acids in previously Soxhlet extracted pottery (62), suggesting that background levels of fatty acids are between 3 and 13 µg/g, and Evershed (4) suggests that levels of residues below 5 µg/g should be considered as background.…”
Section: Contaminationmentioning
confidence: 99%
“…Based on the ability to resolve the individual components of the often complex mixture of lipids found in potsherds, these techniques have been successively used in the identification of natural products such as resins, tars, pitch and beeswax (Aveling & Heron 1999;Hayek et al 1990;Heron et al 1994;Regert et al 1998;. Also, to identify the components of foodstuff processed or stored in ancient vessels (Stern et al 2000;Evershed et al 1991;.…”
Section: Pottery Functionmentioning
confidence: 99%